An Immersive Motor Protocol for Frailty Rehabilitation - Pedroli, Elisa; Cipresso, Pietro; Greci, Luca; Arlati, Sara; Boilini, Lorenzo; Stefanelli, Laura; Rossi, Monica; Goulene, Karine; Sacco, Marco; Stramba-Badiale, Marco; Gaggioli, Andrea; Riva, Giuseppe (Frontiers in Neurology, 2019)
Frailty is a pre-clinical condition that worsens physical health and quality of life. One of the most frequent symptoms of frailty is an increased risk of falling. In order to reduce this risk, we propose an innovative virtual reality motor rehabilitation program based on an immersive tool. All exercises took place in the CAVE, a four-screen room with a stationary bike. The protocol includes two types of exercises for the improvement of balance: “Positive Bike” and “Avoid the Rocks.” We chose evaluation scales related to the functional aspects and subjective perception of balance. Our aim is to prove that our innovative motor rehabilitation protocol is as effective as or more effective than classical rehabilitation.